HUBUNGAN ANTARA LAMA MENDERITA DIABETES MELITUS DENGAN KEJADIAN STROKE DI RSUD ULIN BANJARMASIN - Munirah, Nida; Fajari, Nanang Miftah; Bakhriansyah, Mohammad; Cahyawati, Wiwit Agung Sri Nur; Marisa, Dona (Homeostasis, 2023)
Diabetes mellitus (DM) is a metabolic disorder that if it is left untreated for a long period could lead to various complications such as stroke. The longer duration of DM is predicted to increase the risk of stroke. The purpose of this study was to determine the relationship between the duration of DM with the risk of stroke. This was an analytic observational study with a cross-sectional approach. This study involved 54 DM patients with stroke selected by using total random sampling method and 54 DM patients without stroke selected by using simple random sampling method. Data were obtained from the Borneo Wetland Study on Diabetes 2 (BEST-DIAB 2) database owned by Poliklinik Endokrin RSUD Ulin Banjarmasin. Data were then analyzed by using Chi-square test in a statistical software the SPSS version 26 with 95% of confidence interval.  The results showed that no significant relationship (p=0.501) between the duration of DM with the risk of stroke for patients with DM at RSUD Ulin Banjarmasin.